Left ventricular wall motion abnormalities are associated with stroke recurrence. (7th February 2017) - Choi, Jeong-Yoon; Cha, Jaehyung; Jung, Jin-Man; Seo, Woo-Keun; Oh, Kyungmi; Cho, Kyung-Hee; Yu, Sungwook
Abstract : Objective: To investigate the role of left ventricular wall motion abnormalities (LVWMA), unrelated to high-risk cardioembolic conditions, in stroke recurrence. Methods: This study included consecutive acute ischemic stroke patients. Transthoracic echocardiography was performed as a routine evaluation for stroke patients. The outcomes were the time to recurrent any stroke and ischemic stroke. Results: Among 4, 316 acute ischemic stroke patients, 430 had LVWMA without high-risk cardioembolic sources. The median observation periods of patients at risk of any stroke and ischemic stroke were 24.5 and 24.7 months. During the follow-up, any stroke and ischemic stroke recurrence were observed in 310 (7.2%) and 250 (5.8%) patients. LVWMA were associated with outcomes after adjustment for traditional cardiovascular risk factors, laboratory and imaging variables, and therapeutic interventions (hazard ratio [HR] 1.707, 95% confidence interval [CI] 1.262–2.310 for any stroke; HR 1.709, 95% CI 1.222–2.390 for ischemic stroke). Moreover, LVWMA could still be considered as independent risk factors after correction for covariates that were significantly associated with outcomes in univariable regression (HR 1.747, 95% CI 1.292–2.364 for any stroke; HR 1.704, 95% CI 1.219–2.382 for ischemic stroke). There were no significant interactions between LVWMA and outcomes between the subgroups except for the statin treatment subgroup. Conclusions: This study suggests that LVWMA, even when unassociated with high-risk cardioembolic sources, could be an independent predictor for stroke recurrence in patients with ischemic stroke.